2008
DOI: 10.1016/j.jcis.2008.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of mineral surfaces with simple organic molecules by diffuse reflectance IR spectroscopy (DRIFT)

Abstract: The adsorption of simple organic molecules to mineral surfaces was investigated by Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) and by solution chemical analysis. Salicylic acid, myristic acid or octacosane were deposited from water or hexane onto gamma-alumina and kaolinite, and examined without evacuation or blending with KBr. The DRIFTS results replicated those from ATR-IR, where available, supporting the validity of DRIFTS as a versatile and convenient alternative to ATR. Results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Studies with salicylic acid adsorption onto γ-alumina and kaolinite showed that consistent handling of the samples (so as to maintain the same particle size distribution) allowed selection of a peak and analysis of peak height (or area under the peak) to determine the surface loading of the organic up to the maximum possible with the washing step used. The quantitative spectral analysis was verified by analysis of the spent solution to determine the quantity of remaining salicylic acid [1,2]. The results of the quantitative studies using hexane as the solvent, as reported in our previous papers, are used as a calibration in this present study of competitive adsorption; the adsorption of salicylic acid onto γ-alumina and kaolinite [2] and myristic acid onto γ-alumina [1].…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Studies with salicylic acid adsorption onto γ-alumina and kaolinite showed that consistent handling of the samples (so as to maintain the same particle size distribution) allowed selection of a peak and analysis of peak height (or area under the peak) to determine the surface loading of the organic up to the maximum possible with the washing step used. The quantitative spectral analysis was verified by analysis of the spent solution to determine the quantity of remaining salicylic acid [1,2]. The results of the quantitative studies using hexane as the solvent, as reported in our previous papers, are used as a calibration in this present study of competitive adsorption; the adsorption of salicylic acid onto γ-alumina and kaolinite [2] and myristic acid onto γ-alumina [1].…”
Section: Introductionmentioning
confidence: 76%
“…Both of the selected organic acids were found in previous associated studies [1,2] to adsorb from solution in hexane as carboxylate onto γ-alumina and kaolinite. The results suggest that the surface associated water, present on mineral oxides under ambient conditions, mediates the organic uptake.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations